FIVE CHARACTERISTICS OF AN INDEPENDENT CURRICULUM IN NATURE SCHOOLS - Sari, Widia Wahana; Marlena, Reni; Julhadi, J; Marsela, Adipura Pedro (Proceeding of International Conference of Islamic Education, 2024)
This research aims to find out how the independent curriculum model in Islamic Religious Education at Indonesian natural schools. This goal is in line with the change in the education curriculum from the K-13 curriculum to the independent curriculum. The research was conducted using a qualitative method with a case study approach, this method was chosen by the researcher because the data to be collected and analyzed were in the form of words and sentences. To facilitate researchers in analyzing these data, in this study researchers used qualitative analysis software NVivo 12. Data sources were taken from the principal, deputy curriculum, PAI facilitators, class facilitators and students. In this study, the author found five themes related to the independent curriculum model in Islamic religious education in natural schools. The five themes are: developing students' morals, active learning-based learning, instilling leadership, building students' entrepreneurial abilities, and mastering digital literacy skills. This research only discusses the characteristics of the independent curriculum in learning in natural schools because it has not been widely exposed by expert practitioners and religious education academics.